Relações lineares entre atributos químicos e biológicos indicadores da qualidade do solo associados ao desempenho agronômico na cultura do milho - Rosa, Guilherme Bergeijer da (2022)
Understanding the relationship between soil attributes and the development and growth of maize plants is an important factor for raising grain productivity with sustainability in the production system. The objective of this work was to relate soil quality indicators: biological and chemical attributes with characteristics related to corn grain production in subtropical climates in Brazil. For this, six experiments were carried out in three locations, Frederico Westphalen - RS and Santa Maria - RS in rainfed cultivation; and São Vicente do Sul - RS with central pivot irrigation, in the 2020/2021 crop year, divided into 2 sowing seasons, the first in September and the second in October, totaling six environments (three locations x two sowing seasons). The evaluations carried out were soil chemical analysis (macronutrients + pH, Al and MO), biological analysis (basal soil respiration, soil decomposition rate and soil fauna), yield components (number of rows per ear, number of grains per row and thousand-grain mass) and grain yield. The statistical analyzes used to evaluate the variables were canonical correlations and comparison of means. In the study of canonical correlations, it was observed that the linear dependence between the groups of variables is dependent on meteorological conditions. Under central pivot irrigation, there is a linear dependence between soil biological and chemical indicators. Already under rainfed corn cultivation system between soil biological indicators and corn grain production components. For the study of edaphic entomofauna diversity, it can be observed that the season factor has less influence on the fauna composition than the local factor. Even with differences in the frequency of individuals between the locations, the classification into 4 taxonomic groups corresponds to more than 80% of the individuals collected, with the Araneae and Coleoptera groups corresponding to more than 50% of the relative frequency of individuals observed in the study. The residue decomposition rate, Margalef diversity index and the taxonomic groups Acarina, Araneae, Oligochaeta and Chilopoda had a positive correlation with grain yield. Areas with higher grain yields had favorable conditions for a faster decomposition rate, consequently a greater activity of the organisms and nutrient cycling. Finally, the results in the present study suggest that a broad set of attributes should be considered as indicators of soil quality, since their response is sensitive to environmental conditions.